Performance-Based Contracting in Health : The Experience of Three Projects in Africa - Johannes, Lars; Mullen, Patrick; Okwero, Peter; Schneidman, Miriam (World Bank, Washington, DC, 2012)
Performance-based contracting in health is an example of a results-based financing approach to improving health service delivery. In 2003 and 2004 the Global Partnership on Output-Based Aid (GPOBA) supported the design of three schemes using performance-based contracting in Uganda, the Democratic Republic of Congo, and Rwanda. GPOBA's technical assistance has led to three innovative projects funded by the World Bank and the Canadian International Development Agency (CIDA). This note reviews early lessons from these schemes.